2012
DOI: 10.1371/journal.pone.0050078
|View full text |Cite
|
Sign up to set email alerts
|

LL-37 Induces Polymerization and Bundling of Actin and Affects Actin Structure

Abstract: Actin exists as a monomer (G-actin) which can be polymerized to filaments) F-actin) that under the influence of actin-binding proteins and polycations bundle and contribute to the formation of the cytoskeleton. Bundled actin from lysed cells increases the viscosity of sputum in lungs of cystic fibrosis patients. The human host defense peptide LL-37 was previously shown to induce actin bundling and was thus hypothesized to contribute to the pathogenicity of this disease. In this work, interactions between actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…7E). As we have shown recently (39), the bundling of actin filaments by s-LL-37, especially in the presence of 100 mM or higher concentrations of NaCl, is significantly lower compared with unmodified LL-37. This again points to the importance of the specific LL-37 sequence in the formation of strong hydrophobic bonds at the actin LL-37-actin interface.…”
Section: Cross-linking Of Ll-37 To Actin Competes With Ll-37 To Ll-37mentioning
confidence: 50%
See 4 more Smart Citations
“…7E). As we have shown recently (39), the bundling of actin filaments by s-LL-37, especially in the presence of 100 mM or higher concentrations of NaCl, is significantly lower compared with unmodified LL-37. This again points to the importance of the specific LL-37 sequence in the formation of strong hydrophobic bonds at the actin LL-37-actin interface.…”
Section: Cross-linking Of Ll-37 To Actin Competes With Ll-37 To Ll-37mentioning
confidence: 50%
“…8) and bundling experiments (39) indicates that LL-37 binds to the DNase I binding loop (D-loop) of actin (52). This conclusion was supported by the results of subtilisin cleavage of actin, which showed that the integrity of the D-loop is a prerequisite to the tight binding of LL-37 to actin (Fig.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations